Organizing New Product Development Projects in Strategic Alliances - Gerwin, Donald; Ferris, J. Stephen (Organization Science, 2004)
We utilize research on alliance governance structures and on new product development to study how partners working under an existing alliance governance structure will organize a new product development project. Initially, we consider a contractual alliance doing multiple projects and argue that the critical organization decisions for any project are whether one or both partners should be involved, whether the partners should work with little or considerable interaction, and whether decision-making authority should reside in a project manager or be consensual. Based on the answers to these questions, we identify at least four viable project organization options. We next examine the option that would be selected under conditions involving the alliance's newness, whether a cooperative history exists, and the distribution of skills for the project. Under each condition, we compare the costs and benefits of the options with respect to the underlying transaction costs, potential for learning, and the ability to contribute to developing a social relations network. By allowing variations in time-to-market pressures, the tacit knowledge that a partner can obtain from the project, and the partners' need to work closely together on future projects, we can determine the points at which costs and benefits indicate a switch from one organization option to another. Finally, we indicate how to adjust the theory for it to apply to a contractual alliance doing only one project and to an institutional alliance such as a joint venture.